DECLINING WITH PURPOSE: PSYCHOSOCIAL PREDICTORS OF RESILIENCE. (11th November 2018) - Halpin, S
Abstract: Emotional disturbances are common in people living with mild cognitive impairment or Alzheimer's disease (MCI/AD). Those who remain self-aware frequently experience a unique set of emotional disturbances, such as depression, as a reaction to expectations regarding cognitive decline and non-ideal social environments. Yet a subset of these individuals are resilient, progressing through their condition without emotional pathology. The current study represents a secondary analysis of patient/care partner dyads (N=6) from the Alzheimer's and Emotions study who were found to exhibit resilience. Patients had a range of educational achievement from high school graduate to graduate degree, all lived with their care partner spouses, and experienced mild levels of cognitive impairment (median MMSE= 24; Functional Assessment Staging of Alzheimer's Disease-FAST score= 3.5). Interpretive Phenomenological Analysis was used to delve deeper into the characteristics surrounding these participants. Persons with MCI/AD utilized various strategies to adapt to and find meaning in their life despite their declining cognitive and physical functioning. Adaptation was defined by decisions that participants and their care providers made which aided in their adapting to their changing condition (e.g., appraising one's current abilities, reappraising abilities and putting things into perspective, and adjustment to current level of functioning). Participants found meaning by reminiscing about the things that made their life meaningful in the past, embracing their current identity as someone with MCI/AD, and maintaining familial and non-familial social support relationships. These non-pharmacological strategies might be helpful in developing resilience among a population of persons with MCI/AD despite their changing needs.